Asuhan Kesehatan Gigi Dan Mulut Pada Tn.Z Dengan Kebiasaan Mengunyah Satu Sisi Di Klinik Jurusan Kesehatan Gigi - Hasanah, Ajeng Yusriah; Widyastuti, Tri; Fatikhah, nurul (Jurnal Terapi Gigi dan Mulut, 2024)
Chewing has the benefit of self cleansing so that when you have a habit of chewing only on one side, it causes plaque buildup. Plaque that is not properly cleaned will result in the formation of tartar. Tartar causes discomfort in a person, as well as Mr. Z's client who feels uncomfortable with this tartar. This study aims to determine the results of Dental and Oral Health Care for client Mr.Z with one-sided chewing habits at the Dental Health Department clinic. This research method is a case report with the concept of oral health care which consists of the process of assessment, diagnosis, planning, implementation, and evaluation. After the examination, the diagnosis was stated that there were 5 basic needs that were not met. To fulfill the 5 basic human needs, scalling, stain removal, filling, giving a referral letter to the dentist, counseling with the Chair Side Talk method and Oral Physiotherapy were carried out. The evaluation results show that 8 basic human needs in clients have been met after treatment.